Determinants of housing developer’s performance: a case study of Bumiputera firms - Mastura Jaafar,; Azlan Raofuddin Hj Nuruddin,; Syed Putra Syed Abu Bakar,; Roslinda Ali, (Penerbit Universiti Kebangsaan Malaysia, 2014)
Despite the importance of the housing sector to the nation’s economy, little research has been conducted into the industry. In an industry dominated by Chinese businessmen, it is interesting to explore the factors affecting the performance of the minority players. This study thus focuses on Bumiputera housing developers in Malaysia. Using the mixed method approach, findings are based on the responses from 38 returned questionnaires and 18 interviews with industry players. Our analysis revealed that the performance of Bumiputera housing developers was influenced by the courses they had attended before starting their business, their propensity to take risks, geographical location-concentration strategy, and their close relationship with bankers and officers of local authorities. This study has significant ramifications for indigenous housing entrepreneurship in Malaysia.